2023
DOI: 10.1007/s40263-023-01024-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute Valproate-Induced Encephalopathy in Status Epilepticus: A Registry-Based Assessment

Abstract: Background Valproate-induced encephalopathy (VIE) affects between 0.1% and 2.5% of patients under long-term epilepsy treatment. Its frequency and characteristics in adults with status epilepticus (SE) is, however, unknown. Objective The aim of this study was to characterize the frequency and the clinico-biological characteristics of VIE in adult SE patients. Methods We reviewed all patients included in our institutional SE registry who were treated for an SE episode between November 2021 and February 2023 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…The EEG of patients with sodium valproate encephalopathy lacks specificity, and currently, there is no universally accepted standard for EEG. 6 In this study, 24-h EEG monitoring of patients with symptoms of encephalopathy showed that case 1 presented three-phase waves, while the remaining three cases presented obvious slow waves dominated by theta waves and delta waves, which occurred synchronously in both hemispheres without epileptiform activity ( Table 1 ) which was consistent with previous research reports. There are currently no large-scale clinical studies on sodium valproate encephalopathy.…”
Section: Discussionsupporting
confidence: 91%
“…The EEG of patients with sodium valproate encephalopathy lacks specificity, and currently, there is no universally accepted standard for EEG. 6 In this study, 24-h EEG monitoring of patients with symptoms of encephalopathy showed that case 1 presented three-phase waves, while the remaining three cases presented obvious slow waves dominated by theta waves and delta waves, which occurred synchronously in both hemispheres without epileptiform activity ( Table 1 ) which was consistent with previous research reports. There are currently no large-scale clinical studies on sodium valproate encephalopathy.…”
Section: Discussionsupporting
confidence: 91%